C2H2-Type Zinc Finger Proteins in Brain Development, Neurodevelopmental, and Other Neuropsychiatric Disorders: Systematic Literature-Based Analysis - Al-Naama, Njoud; Mackeh, Rafah; Kino, Tomoshige (Frontiers in Neurology, 2020)
Neurodevelopmental disorders (NDDs) are multifaceted pathologic conditions manifested with intellectual disability, autistic features, psychiatric problems, motor dysfunction and/or genetic/chromosomal abnormalities. They are associated with skewed neurogenesis and brain development in part through dysfunction of the neural stem cells (NSCs) where abnormal transcriptional regulation on key genes play significant roles. Recent accumulated evidence highlights C2H2-type zinc finger proteins (C2H2-ZNFs), the largest transcription factor family in humans, as important targets for the pathologic processes associated with NDDs. In this review, we identified their significant accumulation (74 C2H2-ZNFs: ~10% of all human members) in brain physiology and pathology. Specifically, we discuss their physiologic contribution to brain development particularly focusing on their actions in NSCs. We then explain their pathologic implications to various forms of NDDs, such as morphological brain abnormalities, intellectual disabilities and psychiatric disorders. We found an important tendency that poly-ZNFs and KRAB-ZNFs tend to be involved in the diseases that respectively compromise gross brain structure and human-specific high-order functions. This may be consistent with their characteristic appearance in the course of species evolution and corresponding contribution to these brain activities.